Strategi Glokalisasi Mcdonald’s Indonesia Sebagai Perusahaan Transnasional (TNC) Dalam Adaptasi Menu Lokal Periode 2023-2025 - Akwal Waffi Kariswan; Maulana Fasha Aralea; Sekar Rahayu; Syifa Nindia Destiany; Septianis Afifah (Journal of Legal, Political, and Humanistic Inquiry, 2025)
The glocalization strategy is a crucial factor for transnational corporations adapting to markets with strong cultural characteristics, such as Indonesia. The public's preference for spicy food, rice consumption, and the use of distinctive spices has prompted McDonald's to adapt its menu, including products like Ayam Spicy, Nasi Uduk McD, Sambal Korek, and various pies with local flavors. This article uses a qualitative, literature-based method to analyze data from scientific journals, previous research, media reports, and company documents. This approach helps illustrate how McDonald's integrates its global identity with local cultural elements to increase consumer acceptance. This research demonstrates that menu adaptations serve not solely as a commercial strategy but also as a form of business diplomacy that strengthens McDonald's social legitimacy as a transnational corporation and reduces cultural resistance to global products. Thus, this study confirms that glocalization is a crucial mechanism in global-local dynamics, particularly in the fast food industry, which relies heavily on sensitivity to public tastes.